Pengaruh Electronic Word Of Mouth, Sosial Media Marketing Dan Brand Image Terhadap Keputusan Pembelian Produk Erigo: (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Rizky Febrian; M.Fadhli Nursal; Franciscus Dwikotjo Sri Sumantyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The Influence of Electronic Word of Mouth, Social Media Marketing and Brand Image on Erigo Product Purchasing Decisions (Case Study of 2020 Management Study Program Students, Bhayangkara University, Greater Jakarta) The research conducted aims to determine partially and simultaneously between electronic word of mouth, social media marketing, and brand image on purchasing decisions for Erigo products. This research is research with a quantitative approach. The sampling technique used is saturated sampling. The population in this study were all Erigo consumers in the Management study program Class of 2020, Bhayangkara University, Greater Jakarta with a sample of 155 respondents. Data processing and hypothesis testing used SPSS 23 software. The research results showed that electronic word of mouth partially had a positive and significant effect on purchasing decisions, social media marketing partially had a positive and significant effect on purchasing decisions, and brand image partially had a positive and significant effect. on purchasing decisions. Simultaneous test results show that electronic word of mouth, social media marketing, brand image simultaneously influence purchasing decisions